Proposal for the Utilization of Multilevel Solar Inverters for the Electrical Network Conditioning of a Hospital - Rerhrhaye Badr; Rerhrhaye Fathallah; El Akkary Ahmed; Lahlouh Ilyas; Ennaciri Yassine; Sefiani Nacer; Khouili Driss; El Martaoui Chaymae (EPJ Web of Conferences)
Modern healthcare facility management aims to enhance service quality while optimizing patient and staff comfort. A critical challenge lies in energy consumption, which directly impacts service continuity. Hospitals rely heavily on electricity, leading to high operational costs and disturbances in the electrical network due to power-intensive equipment such as incandescent lamps and transformers. In line with Morocco’s 2030 renewable energy strategy, many hospitals are adopting optimized and hybrid energy management policies. A thorough analysis of hospital electrical networks, alongside compliance with standards such as NFC15-100, ensures improved power quality and supply continuity. This study investigates the implementation of solar inverters for hospital network conditioning, enabling reactive power compensation and active filtering in addition to their primary function of injecting active power. Simulations conducted in a DC/AC multilevel architecture using PLECS demonstrate that replacing three-level NPC inverters with five-level SMC inverters mitigates topology limitations, enhances current quality, and reduces output filter size. The study aims to highlight the advantages of five-level SMC architectures controlled by PI regulators in solar energy applications and power conditioning. Furthermore, a comparative analysis with two-level architectures is presented, followed by an overview of hospital electrical network topologies, a two-stage solar system model, PWM and PI control strategies, and performance evaluation results.